HTA - Algorithm or Process?; Comment on "Expanded HTA: Enhancing Fairness and Legitimacy" - Anthony J. Culyer (Kerman University of Medical Sciences, 2016)
Daniels, Porteny and Urrutia et al make a good case for the idea that that public decisions ought to be made not only "in the light of " evidence but also "on the basis of " budget impact, financial protection and equity. Health technology assessment (HTA) should, they say, be accordingly expanded to consider matters additional to safety and cost-effectiveness. They also complain that most HTA reports fail to develop ethical arguments and generally do not even mention ethical issues. This comment argues that some of these defects are more apparent than real and are not inherent in HTA - as distinct from being common characteristics found in poorly conducted HTAs. More generally, HTA does not need "extension" since (1) ethical issues are already embedded in HTA processes, not least in their scoping phases, and (2) HTA processes are already sufficiently flexible to accommodate evidence about a wide range of factors, and will not need fundamental change in order to accommodate the new forms of decision-relevant evidence about distributional impact and financial protection that are now starting to emerge. HTA and related techniques are there to support decision-makers who have authority to make decisions. Analysts like us are there to support and advise them (and not to assume the responsibilities for which they, and not we, are accountable). The required quality in HTA then becomes its effectiveness as a means of addressing the issues of concern to decisionmakers. What is also required is adherence by competent analysts to a standard template of good analytical practice. The competencies include not merely those of the usual disciplines (particularly biostatistics, cognitive psychology, health economics, epidemiology, and ethics) but also the imaginative and interpersonal skills for exploring the "real" question behind the decision-maker's brief (actual or postulated) and eliciting the social values that necessarily pervade the entire analysis. The product of such exploration defines the authoritative scope of an HTA.